Null Referential Subjects in Övdalian - Rosenkvist, Henrik (Nordic journal of linguistics, 2010)
This article is concerned with the description and analysis of Övdalian referential null subjects. A general background to Övdalian is provided together with the syntactic restrictions on the possible null subjects (wįð ‘we’ and ið ‘you’). Interestingly, these null subjects in Övdalian do not appear in the same syntactic positions. This syntactic difference leads us to the conclusion that the distribution of the two possible null subjects must be explained individually. I argue here that the syntactic restrictions indicate that null wįð requires a link to the surrounding context in order to be identified, whereas the identification of null ið seems to be dependent on the agreement affix. I build on the proposal of Koeneman (2006), and argue that affixes may have pronominal properties, proposing that this gives an explanation as to why null ið is not restricted in the same fashion as null wįð. Finally, Övdalian is discussed in a wider Germanic context, and it is shown that Övdalian is one of a small number of non-standard Germanic languages which allow referential null subjects.